Persistence and Dispersal of Stocked Rainbow Trout in an Alabama Tailwater. (23rd April 2021) - Baker, Sarah M.; Sammons, Steven M.
Abstract: Tailwater trout fisheries provide popular and unique opportunities for anglers across the southeastern USA but often suffer from high mortality and low returns to creel. The Sipsey Fork tailwater in Alabama provides such an opportunity and is stocked monthly with Rainbow Trout Oncorhynchus mykiss . However, a recent creel survey found that less than 25% of fish stocked each month were harvested, with the fate of remaining fish unknown. Thus, movement patterns and fates of four cohorts of stocked Rainbow Trout were examined in the Sipsey Fork using radiotelemetry. Ninety‐two tagged Rainbow Trout travelled an average of 5.8 km (SE = 0.7 km) away from their stocking location. Dam operation rarely appeared to influence trout movement. However, tagged Rainbow Trout rapidly dispersed below where most angler access was located; more than 40% of fish locations were found in this area by 3 weeks poststocking in three of four cohorts. Overall, only 30% of tagged Rainbow Trout remained alive 5 weeks after stocking. Rainbow Trout survival during this 5‐week period ranged from 11% to 74% across cohorts, and those stocked in January exhibited greater survival than those stocked in June or October. Factors affecting trout movement and mediating Rainbow Trout survival may include Striped Bass Morone saxatilis predation, water temperature, and dissolved oxygen concentrations during certain times of the year. Efforts to mitigate such factors by altering stocking schedules could increase longevity of stocked Rainbow Trout and therefore maximize availability of fish to anglers. However, the propensity of stocked fish to migrate below the area of public access will continue to limit catch and harvest from this fishery.